Heavy Metal Levels in Various Fodders in the Periphery of Kolkata, India - Ghosh, Sarbaswarup; Hazra, Aloke; Sahu, Narayan Chandra; Goswami, Rupak; Ghosal, Abhijit; Mukherjee, Anupam (Indian Journal of Animal Nutrition, 2018)
Heavy metal contamination of fodder species is important from epidemiological point of view as it is the entry point of elements to food web. Present study was conducted to examine heavy metal concentration in locally available fodders in the periphery of Kolkata, India. The leaf samples of 8 various fodders (Brachiria mutica, Pennistem purpurium, Trifolium alexandrinum, Zea mays, Sorghum bicolour, Digitaria sanguinalis, Azolla microphylla and Oryza ruphipagan) were taken in triplicates from the field. Soil samples from the same fields were collected to compute transfer factors (Cplant/Csoil). These were analysed for minerals like As, Pb, Cd, Hg, Fe, Cu, Zn and Mn. Moderate level of As was found in all fodder species. Azolla and Dhani grass (Oryza ruphipagan) possessed higher (P<0.05) concentration of As 4.14 and 3.94 ppm, respectively. Lead contamination was higher in all the fodders which could lead to chronic lead poisoning in animals. The transfer factors for Hg and Zn were higher in all type of fodders. Hence, the concentration of essential heavy metal in fodders in the study area was sufficient to meet animal’s requirements. Also, there was a trend towards bioaccumulation of toxic heavy metals particularly that of lead in fodders.